Analisis Miskonsepsi Siswa SMA pada Materi Usaha dan Energi di Kabupaten Kendal - Lestari, Puji; Hayat, M. Syaiful (UPEJ Unnes Physics Education Journal, 2021)
This study aims to describe the analysis of students' misconceptions at SMAN 1 Gemuh Kendal on the matter of work and energy. This research is descriptive with a case study design. The population were all students of class X MIPA SMAN I GEMUH with a sample of class X MIPA1. Data was obtained from multiple choice test instruments in four-tier format that can diagnose students' misconceptions. The results showed that the average misconception experienced by students in the business and energy material was quite a lot because the average percentage obtained was 36.06%. The order of sub-concepts identified as misconceptions from those with the highest percentage are: Energy (38.89%); Business (38.20%); Law of Conservation of Mechanical Energy (34.26%) and Business and Energy Relations (32.885).